Morphological changes induced by testosterone in the mammary glands of female Wistar rats - Chambô-Filho,A. (2005)
Increased levels of androgens in postmenopausal women are considered to be a risk factor for breast cancer. Testosterone, alone or in combination with estrogen, induces epithelial dysplasia and mammary tumors in Noble rats. Since this model of hormone-induced neoplasia has not been reported in other rat strains, we studied the effect of testosterone on the mammary gland morphology of female Wistar rats. Sixty adult, non-castrated, female Wistar rats were implanted in the dorsum midline with a silicone tube containing 50 mg testosterone (testosterone propionate in 30 animals and non-esterified testosterone in the remaining 30 animals) and 20 additional animals were implanted with empty tubes and used as control. Five animals per group were killed 30, 60, 90, 120, 150, and 180 days after implantation, and the mammary glands were dissected, fixed and embedded in paraffin. Histological sections were then stained with hematoxylin and eosin and picrosyrius red for collagen visualization. Morphological and morphometric analysis demonstrated ductal proliferation and acinotubular differentiation with secretory activity in all treated animals, peaking at 90 days of androgen exposure. After 90 days the proliferation of acinar epithelial cells was evident, but there was a progressive reduction of secretory differentiation and an increase in intralobular collagen fibers. There was no morphological evidence of dysplastic changes or other pre-neoplastic lesions. Testosterone treatment applied to adult, non-castrated female Wistar rats induced a mammary gland hyperplasia resembling the lactating differentiation, with progressive reduction in secretory differentiation.